Effect of long-term nanofluid usage on horizontal ground source heat pump performance - Kapicioglu, Abdullah; Esen, Hikmet (Pergamon-Elsevier Science Ltd, 2024)
Nanofluids in thermal systems such as heat pumps are one of the innovative approaches due to their high thermal conductivity. However, nanofluids suffer from effects such as agglomeration and settling. Gravitational sedimentation occurs in the absence of circulation or mean flow conditions; this is a common problem in real-life engineering applications. The current experimental study focuses on how the system performance will be affected in this long standby situation. The study investigated the effect of nanofluid on the system performance in a Nanofluid-Assisted Ground Source Heat Pump (NAGSHP) system, which was examined experimentally long term. The findings show a loss of up to 3 % in the performance of the Ground Heat Exchanger (GHE) and a 2.5 % decrease in the coefficient of performance (COP) of the system. These values are even lower than the results obtained from experiments with ethylene glycol-water (without nanofluid) base fluid in the previous study. These results show that nanofluids cause performance degradation in long standby conditions. Further studies can investigate the interaction between surfactants and nanoparticles that reduce the sedimentation rate, considering different flow conditions, and show the implications of these results in engineering applications.
Keywords: Ground heat exchanger; Ground source heat pump; Nanofluid; Long-term effects; Performance analysis